Percepção do apoio familiar, iniciação sexual e autolesão na adolescência: um estudo utilizando o Health Behavior in School-Aged Children na Região Amazônica no Brasil - Oliveira, Maria Letícia Marcondes Coelho de (2019)
The present study aimed to understand the asociations between perception of family support, sexual iniciation and the practice of self-harm in adolescence. This research is part of a transnational and multicentric project called Health Behavior in School-aged Children (HBSC), and points out the results obtained in the Amazon Region in Brazil. The research was organizad through two studies: The first article entitled “Sexual behavior and perception of family support in adolescents from the Amazon Region in Brazil that aimed to offer an empirical contribuition to the understanding of sexuality of adolescentes with regard to their relationship with their parents. The second article entitled "Self-harm behaviors, psychological adjustment and family relationships in adolescents from the Amazon Region in Brazil", aimed to identify the associations between the practice of self-harm, anxiety and depression and the perception of family support. The instruments used were the Children's Depression Inventory (CDI), the Spence Children's Anxiety Scale (SCAS) and the Questionnaire (HBSC). The sample consisted of 507 students from Rondônia, aged 13 to 15 years. The analysis of the data was performed through means of comparison of mean, percentage (t-test and chi-square) and analysis of variances. The results indicate that young people who have started their sexual life perceived that parents know little of their lives, and those who become selfinflicted have higher rates of depression and anxiety and that the lack of perception of family support correlates directly with the practice of self-harm. Increasing decisionmaking skills and promoting communication with parents can contribute significantly to stimulating the health and well-being of Brazilian youth. A better understanding of mental and emotional health in adolescence will provide adolescents with greater support for their internal conflicts.